Cenas do ofício : experiência dialógica em clínica do trabalho - Ferreira, Marie Julie Braga (2018)
From the theoretical-methodological perspective of the Activity Clinic, we align ourselves with the understanding of work as a means of action for the subjects, a source of expression, of life, an object created into each situation, constructed and reconstructed through the activity. In this sense, we take the lived dimension of work as the experience that happens at the moment when the institution of work, with its norms, carries a potential to act always in the process of being increased and/or diminished, reinventing itself and/or stiffening. The work as an object of study is here considered in this dimension of experience that is always to be given, by experiencing between prescribed work and accomplished work. In this way, we analyze the professional psychologist of social assistance in a military institution, starting from the problematic field that emerges from the conflict between the anxieties experienced by the professional in her work and the delineation of researching, transforming these anxieties into dialogues, as a method for analyzing the work. In this sense, the worker becomes a researcher of her craft. Therefore, we take the worker's demand, with her anxieties in the face of her practice and her work circumstances, in transformation in the context of researching, to take care of her professional activity. Inspired by the methods proposed by the Clinic of Activity - self-confrontation and instruction to the look-alike - we propose two moments of analysis for the professional gender in question, the first, the dialogue between workers of different professional genres, and the second, professional of the same professional gender. We take, however, these two dialogical moments as an exercise, when they metamorphose into scenes, where the generic predicates of the professional activity are questioned, in a rereading of what minimally support us to act or paralyzes us as authors of the craft. In this way, we propose writing as an instrument for analyzing the transpersonal dimension of the craft, having as a guideline the experience of writing as a generic re-signification of the work experience, performing as a device for repositioning between researcher and worker, by placing the worker on the scene to resignify the narratives, confronting them and separating them, in an exercise of mobilization of the professional genre.